Participatory Research with Young Children - Eckhoff, Angela; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents a guiding framework for designing and supporting participatory research with young children. The volume shares detailed approaches to research designs that support collaborative work with young children and teachers in a wide range of early learning environments. It presents conceptual and ethical considerations for participatory work, and explores children$1 (Bs agency through engagement in participatory practices. It examines challenges to accepted practices and understandings of young children, and discusses the analysis and dissemination of participatory work with children. In doing so, the book informs readers about the conceptual understandings and methodological approaches that can be used to support participatory research investigations where the young child is viewed as knowledgeable and capable of sharing unique opinions, interpretations, and understandings of her experiences as embedded within social, cultural, and political worlds. The book sets the stage for early childhood researchers and educators to develop new understandings grounded in post-developmental, critical, and social constructivist theories while exploring supportive methodological approaches. .s
Preface -- Section 1: Conceptual and Ethical Considerations for Participatory Work -- 1. Participation takes many forms: Exploring the frameworks surrounding children$1 (Bs engagement in participatory research -- 2. Ethical considerations in participatory research with young children -- 3. (3z(BYou Have to Sign Here:(3y (BA hermeneutic reading of young children$1 (Bs politeness play -- Section 2: Exploring Children$1 (Bs Agency Through Engagement in Participatory Research Practices -- 4. Participatory research interviewing practices with children -- 5. When students generate questions: Participatory-based reading instruction in elementary classrooms -- 6. My Mom said you can$1 (Bt use my face, but my voice is alright(3y(B: Children as active agents in research utilizing video data -- 7. (3z(BMy treasure box(3y(B: Pedagogical documentation, digital portfolios and children$1 (Bs agency in Finnish early years education -- Section 3: Participatory Research and Challenges to Accepted Practices and Understandings of Young Children -- 8. Participatory research with young children from special populations: Issues and recommendations -- 9. Counternarratives from the margins: School stories in children$1 (Bs voices -- Section 4: Analysis and Dissemination of Participatory Work with Children -- 10. Supporting children$1 (Bs engagement in active dissemination practices -- 11. Learning to become researchers: Towards participation? -- 12. Then and now:$1 (BReflections on Arts-based participatory research with young children.s
Keywords: Child development; Schools; Study skills; Early Childhood Education; Schools and Schooling; Research Skills